INFLUENCE OF ELECTORAL STIMULATION OF NEUROMEDIATOR SYSTEMS’ ACTIVITY ON MODIFICATION OF ANXIOUS CONDUCT OF WHITE RATS - Frolova, G.A.; Fedotova, Yu.O.; Sobolev, V.I. (World of Medicine and Biology, 2010)
Investigational modifications of anxious behaviour at selective stimulation of activity of some neuromediator systems taking into account individual features in elevated plus-maze. It is set that initially high-anxious animals reacted the decline of anxiety on stimulation of activity of the neuromediator systems. Middle anxiety in control of rat exposed an increase anxiety effect during activating of the noradrenergic system and anxiolitic at stimulation of dofaminergic system. Pharmacological stimulation of the cateholamine systems of Deprenil and Maprotilin caused the increase of anxiety at initially low-anxiety rats.